Avaliação da Atividade Antileishmania da Spiranthera odoratissima ST. Hil (Rutaceae) in vitro, in vivo e in silico - Santos, Rogerio Alexandre Nunes dos (2015)
Leishmaniasis is one of the neglected diseases. High cost, systemic toxicity, and diminished efficacy due to development of resistance by the parasites has a negative impact on the current treatment options. Thus, the search for a new, effective and safer antileishmanial drug becomes of paramount importance. Compounds derived from natural products may be a better and cheaper source in this regard. This study evaluated the in vitro, in vivo and in silico antileishmanial activity of Spiranthera odoratíssima (Rutaceae) fractions and isolated compounds, using promastigote and amastigote forms of different Leishmania species. J774 A.1 macrophage was used as the parasite host cell for the in vitro assays. Evaluations of cytoxicity, nitric oxide (NO), interleukin-10, interleukin-12, IFN-γ were obtained in vitro and expression of p38 mitogen activated protein kinase (p38 MAPK), NF-κB (p50 and p65) was studied by western blotting.in vivo and in silico analysis were carried out. In vitro experiments showed that the fruit hexanic fraction (Fhf) and its alkaloid skimmianine (Skm) have a significant (P<0·001) effect against L. braziliensis. This anti-L. braziliensis activity of Fhf and Skm was due to increased production of NO and attenuation of IL-10 production in the macrophages in contrast of IL-12 and IFN-γ levels increased at concentrations ranging from 1·6 to 40·0 μg/ml. Fhf and Skm showed expression of p38 and NF-κB, pathways involved in the production of Th1 cytokines and nitric oxide. In vivo testing showed reduction in lesion size in mice infected with L. braziliensis, as well as reduction in parasite burden in linfonode and spleen. The in silico assay demonstrated significant interaction between Skm and amino acid residues of NOS2.Skm is thus a promising drug candidate for L. braziliensis due to its potent immunomodulatory activity.